Intraoperative Mannitol Use Does Not Improve Long-term Renal Function Outcomes After Minimally Invasive Partial Nephrectomy - Power, Nicholas E. (2012)
OBJECTIVE: To evaluate intravenous mannitol during minimally invasive partial nephrectomy (PN) by comparing the renal function outcomes of the patients who received it versus those who did not. METHODS: Of 285 consecutive elective minimally invasive PN cases from February 2005 to July 2010, 164 patients (58%) were treated with mannitol. We compared the renal function recovery using a multivariate generalized estimating equation linear model of estimated glomerular filtration rate (eGFR) controlling for nephrometry complexity, preoperative eGFR, American Society of Anesthesiologists score, ischemia time, estimated blood loss, age, and sex. Sensitivity analyses were performed to adjust for cold ischemia and individual surgeon differences corrected for year of surgery. RESULTS: Of the 285 patients who underwent minimally invasive treatment, 164 received mannitol and 121 did not. Those who received mannitol had a better preoperative eGFR (median 72 vs 69 mL/min/m(2), P =.046), less complex nephrometry scores (P =0.051), and were less likely to have an American Society of Anesthesiologists score of ≥3 (42% vs 54%, P =.005). Renal function recovery was similar in both groups (estimated effect of mannitol −0.7 mL/min/m(2), 95% confidence interval −3.6-2.2, P =.6). At no point in the postoperative period did mannitol make a significant difference in the eGFR according to the generalized estimating equation model after adjusting for multiple potential renal function confounders. CONCLUSION: Mannitol use did not influence renal function recovery within 6 months of minimally invasive PN as measured by the eGFR in our analysis. An appropriately designed prospective study of mannitol is being conducted to validate its use during PN.